Competency-Based HR Planning and Performance Gaps in Local Cooperatives: Evidence From Cikalong Village, Pangandaran - Muhamad Ecky Kusumah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study seeks to understand how competency-based human resource planning can meaningfully contribute to narrowing the performance gap within local government bureaucracies. Grounded in initial observations of misalignment between ideal and actual employee competencies, the research examines in depth the processes of competency mapping, the range of internal and external barriers encountered, and the ways these dynamics ultimately shape organizational effectiveness. The qualitative approach is employed not merely as a methodological choice, but because interviews, observations, and document analysis capture operational nuances that quantitative data often miss. The findings indicate that when competencies are placed at the core of HR planning, employee placement becomes more objective, organizational accountability strengthens, and the bureaucracy becomes more capable of adapting to the increasing complexity of public service demands. However, it is worth noting that the process is far from seamless. The clarity of competency standards, the reliability of HR information systems, and the adaptability of organizational culture emerge as critical determinants of success. Taken together, the study underscores that competency-based HR planning is not simply a technical procedure but a strategic imperative for local governments aiming to reduce performance gaps and enhance the quality of public sector governance.